A facile method to sensitively monitor chlorinated phenols based on Ru(bpy)32+ electrochemiluminescent system using graphene quantum dots as coreactants. (September 2017) - Qi, Bao-Ping; Zhang, Xiaoru; Shang, Bing-Bing; Xiang, Dongshan; Qu, Wanyun; Zhang, Shenghui
Abstract: Except the tunable photoluminescent property, graphene quantum dots (GQDs) with special structures have also exhibited other novel properties. Herein, GQDs played a novel coreactant role in Ru(bpy)3 2+ /GQDs system to increase the anodic ECL signal of Ru(bpy)3 2+, which has been testified by ultraviolet, fluorescence, and electrochemiluminescence (ECL) experiments. Based on the coreactant mechanism of Ru(bpy)3 2+ /GQDs system, a chlorinated phenol-related quenching ECL sensor was designed and the sensor showed a good linear relationship in the range from 0.60 to 55 μM with the detection limit of 1.4 × 10 −8  M (S/N = 3). These results were not only beneficial to resolve the structure of GQDs, but also expanded the application field of GQDs. Graphical abstract: